Flow investigation in a centrifugal pump - Goh, Yi Fan (2016)
From multiple medical studies on ventricular assist devices, thrombosis and haemolysis within centrifugal blood pumps have shown to be greatly affected by leakage flow characteristics. Leakage flow occurs within the clearance gap between impeller wall and volute wall of a centrifugal pump. Stagnation of blood flow can cause blood to clot while high blood flow rate accompanied by shearing can cause blood to rupture. Leakage flow can also reduce the volumetric efficiency of a centrifugal pump. These effects are undesirable and hence form the study motivation for this project.